2015
DOI: 10.1016/j.brainres.2015.02.053
|View full text |Cite
|
Sign up to set email alerts
|

What goes up, can come down: Novel brain stimulation paradigms may attenuate craving and craving-related neural circuitry in substance dependent individuals

Abstract: Vulnerability to drug related cues is one of the leading causes for continued use and relapse among substance dependent individuals. Using drugs in the face of cues may be associated with dysfunction in at least two frontal-striatal neural circuits: (1) elevated activity in medial and ventral areas that govern limbic arousal (including the medial prefrontal cortex (MPFC) and ventral striatum) or (2) depressed activity in dorsal and lateral areas that govern cognitive control (including the dorsolateral prefron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
159
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(167 citation statements)
references
References 65 publications
5
159
0
3
Order By: Relevance
“…A recent sham-controlled neuroimaging study by our group demonstrated that 3600 pulses of continuous theta burst stimulation (an LTD-like form of TMS) to the left frontal pole/MPFC/BA 10 decreased stimulus-evoked activity in the ventral MPFC and the nucleus accumbens (Hanlon et al, 2015), brain regions typically invoked by drug cues and implicated in cue-primed relapse. The present study demonstrates that, relative to controls, the amplitude of TMS required to evoke a significant BOLD signal in striatal limbic circuitry may be relatively high in the cocaine users.…”
Section: Implications For Treatment Development-ventral Medial Pfc Stmentioning
confidence: 98%
See 3 more Smart Citations
“…A recent sham-controlled neuroimaging study by our group demonstrated that 3600 pulses of continuous theta burst stimulation (an LTD-like form of TMS) to the left frontal pole/MPFC/BA 10 decreased stimulus-evoked activity in the ventral MPFC and the nucleus accumbens (Hanlon et al, 2015), brain regions typically invoked by drug cues and implicated in cue-primed relapse. The present study demonstrates that, relative to controls, the amplitude of TMS required to evoke a significant BOLD signal in striatal limbic circuitry may be relatively high in the cocaine users.…”
Section: Implications For Treatment Development-ventral Medial Pfc Stmentioning
confidence: 98%
“…The data that emerge from this experiment may provide a neurobiological basis for the emerging data that a potentiating form of repetitive transcranial magnetic stimulation (TMS) to the DLPFC ( (Camprodon et al, 2007;Politi et al, 2008;Terraneo et al, 2016), or an attenuating form of TMS to the MPFC (Hanlon et al, 2015) appears to dampen craving among cocaine users. To minimize the impact of the methodological and human subject's factors, we employed an experimental technique that activates the prefrontal cortex (like many task-based studies) without requiring the individual to concentrate on a task.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It suggests that addiction could be associated with abnormal interactions between the rewarding process and cognitive control. The elevated limbic arousal response in nucleus accumbens combined with a depressed cognitive control function in DLPFC might re- 198 sult in uncontrolled addictive behavior under rewarding cue [46] . This study revealed that subjects with IGD had significantly lower FC with the right nucleus accumbens over the left DLPFC and right insula.…”
Section: The Functional Connection Of the Nucleus Accumbensmentioning
confidence: 99%